Integrasi Prinsip Etika Profesional dalam Data Governance untuk Mendukung Keamanan dan Akurasi Informasi di Era Digital - Parhusip, Jadiaman; Michael, Michael (UNIVERSITAS SERAMBI MEKKAH, 2025)
In the digital era, data integrity and security serve as the cornerstone for ensuring the accuracy of information generated by computing systems. This article examines the importance of professional ethical principles adopted from the Computing Curricula 2020 in the practice of data governance. Focusing on a case study of ethical violations in financial reporting, this research aims to provide guidance on implementing ethical standards in data management across various sectors. The research methodology involves a literature review to identify the correlation between ethical practices and the quality of computational outcomes. The findings indicate that integrating ethics into information technology can minimize the risk of data manipulation and enhance public trust in digital systems